Social Media Research in India: A Scientometric Assessment of Publications Output during 2004-13 - Gupta, Ritu; Gupta, B. M. (Journal of Information and Knowledge, 2015)
Examines 733 Indian publications on social media research, as covered in Scopus database during 2004-13, experiencing an annual average growth rate of 168.31% and citation impact of 1.27. The world social media research output came from several countries, of which the top 15 accounts for 81.95% share of the global output during 2004-13. India’s global publication share was 1.97% during 2004-13 and hold 13th rank in global publication output. Only 37.38% of Indian publications on social media were cited one or more times since their publication till March 2015. India’s social media research output came from several organizations and authors, of which the top 10 contributed 30.42% and 17.87% share respectively of its total output during 2004-13. India’s international collaborative share in social media was 22.10% during 2004-13. The paper stressed the need for the development of a national social media policy by Indian government.